Becoming flood insecure: Lessons from village level experiences in Tana Delta, Kenya. (December 2022) - Okoko, Anita Nyapala
Abstract: Floods affect the human security conditions of floodplain residents. The aim of this paper is to explore how residents of the Tana River Delta in Kenya become flood insecure. This paper utilises assemblage theory, particularly the principles of rhizomatic multiplicity to explain the concept of becoming flood insecure. It combines these rhizomatic multiplicity principles with disruptions to the pillars of human security which are becoming afraid, becoming wanting and becoming undignified and their composite conditions of human insecurity to create an analytical framework with which to understand becoming flood insecure. The study sources its data from Focus Group Discussions in 10 sampled villages in the Tana River Delta. The results reveal that becoming flood insecure is a rhizomatic multiplicity and that the pillars and conditions of human security that comprise it are heterogenous and interconnected. The results reveal the conditions of human insecurity in the Tana River Delta as personal, food, water, fuel, housing, health, environment, and political. They also reveal that while children become more flood insecure, they are also the most adaptive. Additionally, the results show that there are transitory conditions of human insecurity, food, housing health, to which people attempt to find local solutions and redundant conditions of human insecurity, political, health, water, personal and environment, to which people cannot find local solutions and public action is required. Highlights: Becoming flood insecure is a rhizomatic multiplicity. It is context-dependent on the assemblage of spatiotemporal conditions. Flood security should be dynamic in relation to each assemblage of becoming flood insecure.